Preservation of Facial Nerve With Adjuvant Radiotherapy for Recurrent Mammary Analogue Secretory Carcinoma of Parotid Gland. Issue 4 (June 2016) - Jin, Shufang; Ma, Hailong; He, Yue
Abstract : Abstract: Mammary analogue secretory carcinoma of salivary glands harbors the recurrent ETV6-NTRK3 gene fusion because of the translocation t (12; 15) (p13; q25) and resembles breast secretory carcinoma. This tumor composed of papillary, cystic, solid, and cribriform patterns. Immunohistochemically, the tumors are positive for mammaglobin, CK7, CK8, STAT5a, vimentin, and S100. In this report, the authors presented a patient of recurrent parotid gland mammary analogue secretory carcinoma in a 22-year-old woman. The patient received extended parotidectomy with partial adhesive masseter surgery. The facial nerve was preserved during the surgery and adjuvant radiotherapy was performed postoperation. The patient did not suffer local recurrence and facial paralysis in the 18 months follow-up period.